2019
DOI: 10.3390/jcm8071070
|View full text |Cite
|
Sign up to set email alerts
|

ATP Synthase Subunit Epsilon Overexpression Promotes Metastasis by Modulating AMPK Signaling to Induce Epithelial-to-Mesenchymal Transition and Is a Poor Prognostic Marker in Colorectal Cancer Patients

Abstract: Metastasis remains the major cause of death from colon cancer. We intend to identify differentially expressed genes that are associated with the metastatic process and prognosis in colon cancer. ATP synthase epsilon subunit (ATP5E) gene was found to encode the mitochondrial F0F1 ATP synthase subunit epsilon that was overexpressed in tumor cells compared to their normal counterparts, while other genes encoding the ATP synthase subunit were repressed in public microarray datasets. CRC cells in which ATP5E was si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 41 publications
(59 reference statements)
1
14
0
Order By: Relevance
“…ATP plays an important role in regulating tumor cell invasion and EMT (Yang et al, 2019). It has been found that extracellular ATP could modulate the MAPK signaling pathway to induce EMT and promote colon cancer cell metastasis (Huang et al, 2019). This study also found that ATP could induce EMT and promoted the metastasis of colon cancer cells.…”
Section: Discussionsupporting
confidence: 54%
“…ATP plays an important role in regulating tumor cell invasion and EMT (Yang et al, 2019). It has been found that extracellular ATP could modulate the MAPK signaling pathway to induce EMT and promote colon cancer cell metastasis (Huang et al, 2019). This study also found that ATP could induce EMT and promoted the metastasis of colon cancer cells.…”
Section: Discussionsupporting
confidence: 54%
“…The altered expression of mt-ND2 is critical to multiple disease in human [ 25 , 26 ]. ATP synthase epsilon subunit (ATP5E) gene was found to encode the mitochondrial F0F1 ATP synthase subunit epsilon [ 27 ]. In addition, ATP5E was proven to be required for normal spindle orientation during embryonic divisions in Drosophila [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Colon cancer cells in which the ε subunit was silenced showed markedly reduced invasive and migratory abilities and ATP5E gene downregulation significantly reduced the incidence of distant metastasis in a mouse xenograft model, suggesting an additional role of the upregulation of some ATP synthase subunits in a more invasive phenotype. In these colon cancer samples the ε subunit level was associated with the AMPK-AKT-HIF1 signalling axis, while its silencing led to the degradation of HIF1α under hypoxia through AMPK-AKT signalling (Huang et al 2019). On the same line, much higher mRNA levels of the OSCP subunit of ATP synthase were detected in a metastatic stomach cancer cell line than in a non-metastatic cancer cell line, that were obtained from the same patient (Salesiotis et al 1995).…”
Section: Expression Of Atp Synthase In Cancermentioning
confidence: 93%
“…Oligomycin treatment prevents differentiation in the HaCaT cell model, which correlates with a decrease in mitochondrial ATP content, supporting the idea that the observed increase in the ATP synthase catalytic subunit has a role in promoting oxidative phosphorylation during HaCaT differentiation. The overexpression of ε subunit encoded by the ATP5E gene was detected in colorectal cancer cells from patients, compared to their normal counterparts ( Figure 2) (Huang et al 2019). Colon cancer cells in which the ε subunit was silenced showed markedly reduced invasive and migratory abilities and ATP5E gene downregulation significantly reduced the incidence of distant metastasis in a mouse xenograft model, suggesting an additional role of the upregulation of some ATP synthase subunits in a more invasive phenotype.…”
Section: Expression Of Atp Synthase In Cancermentioning
confidence: 95%